2018
DOI: 10.1371/journal.pone.0202495
|View full text |Cite|
|
Sign up to set email alerts
|

Differential changes in the onset of spring across US National Wildlife Refuges and North American migratory bird flyways

Abstract: Warming temperatures associated with climate change can have indirect effects on migratory birds that rely on seasonally available food resources and habitats that vary across spatial and temporal scales. We used two heat-based indices of spring onset, the First Leaf Index (FLI) and the First Bloom Index (FBI), as proxies of habitat change for the period 1901 to 2012 at three spatial scales: the US National Wildlife Refuge System; the four major bird migratory flyways in North America; and the seasonal ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…In the East, the pattern of advancing thresholds occurring at higher latitudes and not at lower latitudes is consistent with other studies reporting an increasing "speed of spring," where the span of time between when a single threshold is met at lower latitudes or elevations and when it is met at higher latitudes or elevations is decreasing (Asse et al, 2018;Post et al, 2018;Vitasse et al, 2018). Attributed primarily to a slower rate of warming in the Southeastern United States (Ault et al, 2015;Meehl et al, 2012;Pan et al, 2004;Schwartz et al, 2006;Waller et al, 2018), the pattern observed in this study is anticipated to persist into the future (Jeong et al, 2013;Wuebbles et al, 2017).…”
Section: Timing Of Thresholds Across Latitude and Elevation Is Being Compressed In The East And Expanded In The Westsupporting
confidence: 87%
See 3 more Smart Citations
“…In the East, the pattern of advancing thresholds occurring at higher latitudes and not at lower latitudes is consistent with other studies reporting an increasing "speed of spring," where the span of time between when a single threshold is met at lower latitudes or elevations and when it is met at higher latitudes or elevations is decreasing (Asse et al, 2018;Post et al, 2018;Vitasse et al, 2018). Attributed primarily to a slower rate of warming in the Southeastern United States (Ault et al, 2015;Meehl et al, 2012;Pan et al, 2004;Schwartz et al, 2006;Waller et al, 2018), the pattern observed in this study is anticipated to persist into the future (Jeong et al, 2013;Wuebbles et al, 2017).…”
Section: Timing Of Thresholds Across Latitude and Elevation Is Being Compressed In The East And Expanded In The Westsupporting
confidence: 87%
“…However, even excluding the strongly advancing thresholds in the Southwest, this pattern of a decrease in the "speed of spring" in the West across latitude and elevation in the thresholds evaluated persists. In a similar evaluation of changes in the start of the spring season, Waller et al (2018) reported no trends across latitude in the Western United States; however, the temporal extent of the study encompassed the entire 20th century, and the metric used, the Spring Leaf Index (Schwartz et al, 2006), represented the leading edge of the spring season. The varying rates of change observed across latitudes have implications for migratory birds and insects seeking resources across the gradient (Armstrong et al, 2016;Waller et al, 2018).…”
Section: Timing Of Thresholds Across Latitude and Elevation Is Being mentioning
confidence: 99%
See 2 more Smart Citations
“…, Waller et al. ). However, long‐term observational records of plant phenology are geographically limited, and new monitoring programs require years of records before researchers can track trends in phenological responses to variations in spring temperatures.…”
Section: Introductionmentioning
confidence: 98%